(untitled) (International journal of medical sciences, 2025)
Sleep is one of the most essential physiological processes ensuring the homeostatic stability of the human body. It plays a crucial role in the optimal functioning of the central nervous system, endocrine system, immune system, and metabolic pathways. Prolonged sleep deprivation acts as a significant stress factor on the body’s major homeostatic systems. Insufficient sleep enhances systemic inflammation through activation of the hypothalamic–pituitary–adrenal (HPA) axis, continuous stimulation of the sympatho-adrenal system, and disruption of cytokine balance.